Should you publish in electronic journals? - Aldrin E. Sweeney (Universidade Estadual de Campinas, 2001)
The rapid growth of information and communication technology since the early 1990s has greatly influenced the accessibility of information on a global level and also has played a critical role in restructuring the mechanisms by which specialized academic knowledge is validated, distributed, and made available to consumers. The primary mechanism for validation and distribution of academic knowledge is that of peer-reviewed publication, and it is this mechanism and its intersection with Internet-based electronic publishing that constitute the focus of this study of attitudes toward scholarship presented in electronic formats.